Pengaruh Experiential Marketing Dan Brand Trust Terhadap Loyalitas Melalui Kepuasan Pelanggan di Z Aesthetic By dr. Zunaila Tebing Tinggi - Putri, Nina Rianda; Himawati, Bella; Purba, Rakhmawati (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
This study aims to determine the effect of Experiential Marketing and Brand Trust on Loyalty Through Customer Satisfaction at Z Aesthetic By Dr. Zunaila Tebing Tinggi. The effects to be known are direct and indirect effects. This type of research is quantitative descriptive. The population in the study was taken from the average number of visitors to the Z Aesthetic By Dr. Zunaila beauty clinic every month as many as 65 customers using the accidental sampling technique. The test tool used was SmartPLS Software version 3.0. From the results of the test, it can be concluded that experiential marketing does not affect customer loyalty, brand trust affects customer loyalty, experiential marketing affects customer satisfaction, brand trust affects customer satisfaction and customer satisfaction affects customer loyalty at the Z Aesthetic By Dr. Zunaila Tebing Tinggi beauty clinic. While customer satisfaction is able to mediate experiential marketing on customer loyalty and customer satisfaction is able to mediate brand trust on customer loyalty at the Z Aesthetic By Dr. Zunaila Tebing Tinggi beauty clinic